Targeting PD-L2–RGMb overcomes microbiome-related immunotherapy resistance - Park, Joon Seok; Gazzaniga, Francesca S.; Wu, Meng; Luthens, Amalia K.; Gillis, Jacob; Zheng, Wen; LaFleur, Martin W.; Johnson, Sarah B.; Morad, Golnaz; Park, Elizabeth M.; Zhou, Yifan; Watowich, Stephanie S.; et al. (Nature (London), 2023)
The gut microbiota is a crucial regulator of anti-tumour immunity during immune checkpoint inhibitor therapy. Several bacteria that promote an anti-tumour response to immune checkpoint inhibitors have been identified in mice 1 – 6 . Moreover, transplantation of faecal specimens from responders can improve the efficacy of anti-PD-1 therapy in patients with melanoma 7 , 8 . However, the increased efficacy from faecal transplants is variable and how gut bacteria promote anti-tumour immunity remains unclear. Here we show that the gut microbiome downregulates PD-L2 expression and its binding partner repulsive guidance molecule b (RGMb) to promote anti-tumour immunity and identify bacterial species that mediate this effect. PD-L1 and PD-L2 share PD-1 as a binding partner, but PD-L2 can also bind RGMb. We demonstrate that blockade of PD-L2–RGMb interactions can overcome microbiome-dependent resistance to PD-1 pathway inhibitors. Antibody-mediated blockade of the PD-L2–RGMb pathway or conditional deletion of RGMb in T cells combined with an anti-PD-1 or anti-PD-L1 antibody promotes anti-tumour responses in multiple mouse tumour models that do not respond to anti-PD-1 or anti-PD-L1 alone (germ-free mice, antibiotic-treated mice and even mice colonized with stool samples from a patient who did not respond to treatment). These studies identify downregulation of the PD-L2–RGMb pathway as a specific mechanism by which the gut microbiota can promote responses to PD-1 checkpoint blockade. The results also define a potentially effective immunological strategy for treating patients who do not respond to PD-1 cancer immunotherapy. Interactions between programmed death ligand 2 (PD-L2) and its binding partner RGMb are downregulated by the gut microbiota, a mechanism that may be exploited to enhance the efficacy of PD-1-based cancer immunotherapies.